Electron push-pull effects induced performance promotion in covalent organic polymer thin films-based memristor for neuromorphic application - Zhou, Panke (2024)
Covalent organic polymer (COP) thin film-based memristors have generated intensive research interest, but the studies are still in their infancy. Herein, by controlling the content of hydroxyl groups in the aldehyde monomer, Py-COP thin films with different electronic push-pull effects were fabricated bearing distinct memory performances, where the films were prepared by the solid-liquid interface method on the ITO substrates and further fabricated as memory devices with ITO/Py-COPs/Ag architectures. The Py-COP-1-based memory device only exhibited binary memory behavior with an ON/OFF ratio of 1:101.87. In contrast, the device based on Py-COP-2 demonstrated ternary memory behavior with an ON/OFF ratio of 1:100.6:103.1 and a ternary yield of 55%. The ternary memory mechanism of the ITO/Py-COP-2/Ag memory device is most likely due to the combination of the trapping of charge carriers and conductive filaments. Interestingly, the Py-COPs-based devices can successfully emulate the synaptic potentiation/depression behavior, clarifying the programmability of these devices in neuromorphic systems. These results suggest that the electronic properties of COPs can be precisely tuned at the molecular level, which provides a promising route for designing multi-level memory devices.